“PENGARUH RETURN ON ASSET, DEBT TO EQUITY RATIO, EARNING PER SHARE, DAN CURRENT RATIO TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014 S/D 2016” - Dwi Prasetyo Wahyu Nugroho, 14.05.52.0133; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2018)
This research is a study that analyzes the effect of return on assets, debt to equity ratio, earnings per share, and current ratio to stock returns in manufacturing companies listed on the Indonesia Stock Exchange in 2014 to 2016. This study uses purposive sampling method in sample selection. Based on the sample criteria, a sample of 222 companies was obtained to 175 during the three-year observation period. The analytical tool used is a multiple linear regression analysis method. The results showed that the variable return on assets had a significant positive effect on stock returns, the variable debt to equity ratio had no significant positive effect on stock returns, variable earnings per share and the current ratio had no significant negative effect on stock returns. Keywords: Stock Return, Return on Asset, Debt to Equity Ratio, Earning Per Share, Current Ratio